PROGRAM BANTUAN MODAL BERBASIS DUSUN DAN RUKUN WARGA PERSPEKTIF SIYASAH SYAR’IYYAH - Masyita, Masyita; Talli, Abdul Halim (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar’iyyah, 2022)
This study aims to examine the provision of Hamlet-Based Capital Assistance and Community Associations in Bantaeng Regency. The writing method used is qualitative writing with a juridical and normative syar’i approach. The results showed that the Hamlet-Based Capital Assistance program and Community Pillars are regulated in Regent Regulation Number 20 of 2019, and the process starts from the stage of exploring dominant businesses in each hamlet /community harmony, deliberation at the hamlet / community harmony level, factual verification by the village / kelurahan government, deliberation at the village / kelurahan level, entrepreneurship training held by the Village Community Empowerment Office, and the last process is the distribution of funds carried out by the Cooperative Service. In the perspective of siyasah syar’iyyah, the program is a noble effort and Islam obliges the government to strive to alleviate poverty and unemployment, so that the program is very relevant and in line with the principle of benefit.